1992
DOI: 10.1136/bjo.76.9.545
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathological findings in conjunctival cells using immunofluorescence staining of impression cytology specimens.

Abstract: The conventional technique of impression cytology provides a non-invasive method for the evaluation of conjunctival epithelium alterations. Using indirect immunofluorescence procedures two inflammatory markers, class I MHC antigens HLA DR and the receptor to IgE (CD23), were sought in impression cytology specimens obtained from 80 patients. In normal subjects conjunctival epithelial cells did not show any reactivity. Only scattered dendritic cells were found to express class U antigens but not the receptor to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 14 publications
1
54
0
2
Order By: Relevance
“…In addition, inflammation may finally influence tear film components other than those depending on the lacrimal gland, as interferon gamma, a major cytokine known to induce both HLA DR expression and apoptosis in conjunctival cells (13) , which has been shown to inhibit mucus production in the airways. Studies using immunological techniques have indeed shown the presence of conjunctival inflammation in more than 80% of patients with keratoconjunctivitis sicca (KCS) (17)(18) . The presence of inflammatory cell infiltrates in the lacrimal glands and the conjunctiva, the upregulation of immune-related antigens and inflammatory cytokines at the level of the conjunctival epithelium, impaired apoptotic regulation of lacrimal glands, and possible alterations in membrane trafficking of acinar cells, in association with squamous metaplasia and loss of globet cells, are common features of KCS (13,15,18) .…”
Section: Pathogenesis Of Dry Eyementioning
confidence: 99%
“…In addition, inflammation may finally influence tear film components other than those depending on the lacrimal gland, as interferon gamma, a major cytokine known to induce both HLA DR expression and apoptosis in conjunctival cells (13) , which has been shown to inhibit mucus production in the airways. Studies using immunological techniques have indeed shown the presence of conjunctival inflammation in more than 80% of patients with keratoconjunctivitis sicca (KCS) (17)(18) . The presence of inflammatory cell infiltrates in the lacrimal glands and the conjunctiva, the upregulation of immune-related antigens and inflammatory cytokines at the level of the conjunctival epithelium, impaired apoptotic regulation of lacrimal glands, and possible alterations in membrane trafficking of acinar cells, in association with squamous metaplasia and loss of globet cells, are common features of KCS (13,15,18) .…”
Section: Pathogenesis Of Dry Eyementioning
confidence: 99%
“…A new definition of this disease has been developed recently, due to evidence which supports that inflammation has a key role in the development of dry eye. [2][3][4][5] Dry eye is a multifactorial disease of the tears and ocular surface that results in symptoms of discomfort, visual disturbance, and tear film instability with potential damage to the ocular surface. It is accompanied by increased osmolarity of the tear film and inflammation of the ocular surface.…”
Section: Introductionmentioning
confidence: 99%
“…HLA-DR is thus considered a proinflammatory marker, and it is specifically upregulated in patients with severe DED. In 1992, Baudouin et al showed that IC could specifically detect HLA-DR expression in human conjunctival cells [11]. Then, in 1997 Baudouin demonstrated HLA-DR quantification via IC, using flow cytometry [25].…”
Section: Dry Eye Disease and Inflammatory Markers Hla-drmentioning
confidence: 99%
“…More recently, however, researchers have used IC to examine specific markers of inflammation, for example, HLA-DR, ICAM-1 and CD8 [10][11][12], and to examine novel biomarkers of dry eye disease (DED). The latter is performed in an attempt to understand the mechanisms underpinning DED pathophysiology and is now feasible, due to vast improvements in the assay sensitivities for gene and protein examination [13].…”
mentioning
confidence: 99%